Count me in - Bajaj, Varsha (Nancy Paulsen Books, 2019)
"Told from two viewpoints, sixth-graders Karina and Chris use social media to stand up to racism in Houston, Texas, after an attack puts Karina's Indian American grandfather in the hospital"--Provided by publisher.